Development of in-situ fatigue crack observing system for rotating bending fatigue testing machine (Fracture and Structural Integrity, 2015)
To substitute for a traditional replication technique, an in-situ fatigue crack observing system for rotating bending testing machine has been newly developed. For verifying performance of this observing system, fatigue tests were carried out by using fatigue specimen having a small artificial defect. It is proved that this system can be detect a small fatigue crack and its propagation behavior.
Keywords: In-situ observation; Fatigue crack initiation; Fatigue crack propagation